Impact of Cancer Cachexia Progression on OATP1B1 Transport Activity: Quantitative Analysis Using Coproporphyrin-I as an Endogenous Biomarker - Sumimoto, Takahiro; Tanaka, Ryota; Suzuki, Yosuke; Negami, Jun; Sueshige, Yoshio; Oda, Ayako; Shiraiwa, Ken; Inagaki, Takashi; Nishikawa, Kazuo; Tatsuta, Ryosuke; Otsu, Satoshi; Ogata, Masao; et al. (Clinical pharmacology and therapeutics, 2025)
Genetic factors, inflammatory cytokines such as interleukin (IL)-6 and tumor necrosis factor-α (TNF-α), and uremic substances such as 3-carboxy-4-methyl-5-propyl-2-furanpropanoic acid (CMPF) have been reported to affect organic anion transporting polypeptide (OATP)1B1 transport activity. However, the relationship between OATP1B1 transport activity and these factors in patients with cancer cachexia has not been reported. This study aimed to identify the factors contributing to individual differences in OATP1B1 transport activity in patients with cancer cachexia, using coproporphyrin-I (CP-I) as an endogenous biomarker of OATP1B1 transport activity. The study recruited 114 patients with cancer cachexia who satisfied the selection criteria. The subjects were classified into pre-cachexia, cachexia, and refractory cachexia. Median [interquartile range] plasma CP-I level was higher in patients with pre-cachexia (0.91 [0.67-1.12] ng/mL) compared with the data in the general population reported previously and tended to be higher in patients with refractory cachexia (1.06 [0.78-1.64] ng/mL) than in those with cachexia (0.87 [0.62-1.07] ng/mL), suggesting that OATP1B1 transport activity may decrease with the progression of cancer cachexia. Plasma CP-I correlated positively with IL-6 and TNF-α concentrations but did not correlate with OATP1B1 polymorphisms or CMPF concentration, which have been reported to reduce transport activity. Multiple regression analysis using the forced entry method identified refractory cachexia as a significant factor independently affecting plasma CP-I concentration. These findings suggest that the reduction in OATP1B1 transport activity in patients with cancer cachexia may be attributed to inflammatory cytokines or some other factors that are elevated by cancer cachexia progression, rather than OATP1B1 polymorphisms and CMPF.